2018
DOI: 10.1186/s13104-018-3796-5
|View full text |Cite
|
Sign up to set email alerts
|

The burden of low back pain among undergraduate physiotherapy students at the University of Zimbabwe: a cross-sectional study

Abstract: ObjectiveGlobally, non-specific low back pain (NSLBP) is a common cause of morbidity in all people including physiotherapy students. However, no study has investigated the problem among undergraduate physiotherapy students in Zimbabwe. This study was conducted, therefore, to provide evidence of the prevalence, clinical characteristics and consequences of recurrent NSLBP among undergraduate physiotherapy students at the University of Zimbabwe.ResultsThe final sample had 90 participants, giving a study response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Alternatively, the higher risk of LBP may reflect the cumulative impacts of physical and psychological factors (eg, anxiety, stress) 6,15,19,35,36 on LBP development in these students. Although final year students are older, age is not necessarily a significant risk factor for LBP in young adults 11 or university students 43,44 . Therefore, the higher prevalence of LBP in final year nursing and medical students may be program specific and triggered by some aforementioned factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the higher risk of LBP may reflect the cumulative impacts of physical and psychological factors (eg, anxiety, stress) 6,15,19,35,36 on LBP development in these students. Although final year students are older, age is not necessarily a significant risk factor for LBP in young adults 11 or university students 43,44 . Therefore, the higher prevalence of LBP in final year nursing and medical students may be program specific and triggered by some aforementioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although final year students are older, age is not necessarily a significant risk factor for LBP in young adults 11 or university students. 43,44 Therefore, the higher prevalence of LBP in final year nursing and medical students may be program specific and triggered by some aforementioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…This study's findings showed that LBP had a significant impact on various domains, including physical, Emotional, and Social health. A study done among physiotherapy students in Zimbabwe reported a lifetime prevalence of LBP to be 56.7% and showed a significant association in lowering physical disability [36] . University students are at higher risk of developing LBP due to improper posture, reduced physical activity, sedentary lifestyle, and physiological stress [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…The total score is then expressed as a percentage, with higher scores indicating greater disability. Disability levels were categorized as minor (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), modest (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), severe (25-34), and complete (35-50). The Oswestry Disability Index (ODI) has demonstrated good test-retest reliability, with an Intraclass Correlation Coefficient (ICC) ranging from 0.72 to 0.98, and a Cronbach's alpha value of 0.89, reflecting excellent internal consistency (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…These endeavors are designed to enhance the well-being of undergraduate physiotherapy students, ensuring their success in academic and professional endeavors. By offering detailed insights and information, this article contributes significantly to the understanding of LBP in both clinical and academic settings (7,8).…”
Section: Introductionmentioning
confidence: 99%